Definitely Hispanic : growing up Latino and celebrating what unites us - James, LeJuan; Molinari, Cecilia (Atria Books, 2019)
"Perfect for fans of Fresh Off the Boat's situational humor and Jane the Virgin's celebration of Latinidad, Definitely Hispanic is a collection of introspective memoiristic essays by social media influencer and viral phenomenon LeJuan James about growing up Hispanic in the US"--